2009
DOI: 10.1007/s11101-009-9153-5
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemistry of heather (Calluna vulgaris (L.) Hull) and its altitudinal alteration

Abstract: Calluna vulgaris (L.) Hull (heather) is the only species within the genus Calluna (Ericaceae). It is a dominant species of heather communities and can be found in most parts of Europe and Northern America from lowland up to alpine regions. Common heather is traditionally used to treat urinary tract disturbances and inflammatory related disorders. This review covers the current knowledge on phytochemical investigations of C. vulgaris which revealed a complex pattern of flavonoid glycosides including acetylated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 45 publications
(47 reference statements)
1
19
1
Order By: Relevance
“…In addition, environmental factors, like altitude [67,68], soil composition, temperature, and humidity [69][70][71], can have a strong impact on the qualitative and quantitative compositions of phytochemicals in a plant. Many of these factors can be more effectively controlled when herbal materials are grown in cultivation; however, in any case, a detailed knowledge about the impact of these factors is necessary in order to achieve optimum results.…”
Section: Adulteration and Substitutionmentioning
confidence: 99%
“…In addition, environmental factors, like altitude [67,68], soil composition, temperature, and humidity [69][70][71], can have a strong impact on the qualitative and quantitative compositions of phytochemicals in a plant. Many of these factors can be more effectively controlled when herbal materials are grown in cultivation; however, in any case, a detailed knowledge about the impact of these factors is necessary in order to achieve optimum results.…”
Section: Adulteration and Substitutionmentioning
confidence: 99%
“…6,12 The content in phenolic compounds can be influenced by the environmental conditions, such as the stress level that plants are subjected during their development, by the altitude and by the harvest season. 15 The study of the influence of altitude in terms of bioactive compounds, have demonstrated that plants growing in lower altitudes present lower amounts of phenolic compounds and, consequently lower antioxidant capacity. 16 Extracts of heather roots, obtained by an hydromethanolic (80:20) extraction, revealed the presence of catechins and procyanidins.…”
Section: Introductionmentioning
confidence: 99%
“…16 Extracts of heather roots, obtained by an hydromethanolic (80:20) extraction, revealed the presence of catechins and procyanidins. 15 Triterpenoids such as ursolic and oleanolic acids were identified in chloroform extracts of cuticular waxes of heather flowers and leaves and have different biological activities, particularly antiinflammatory activity. 17 A study on the antibacterial activity of different aqueous (infusion and decoction) and organic extracts (n-hexane, dichloromethane, ethyl acetate, acetone and methanol) was recently conducted by some of the authors, 11 and as result of the high demonstrated potential, in the present study the acetone extract was fractionated by gradient elution 5 through column chromatography on silica gel.…”
Section: Introductionmentioning
confidence: 99%
“…C. vulgaris can be found in most parts of Europe and Northern America from lowland up to alpine regions. Plant is traditionally used to treat urinary tract infection and infl ammatory disorders [1].…”
Section: Introductionmentioning
confidence: 99%